(untitled) (Research, Society and Development, 2022)
This paper is a Systematic Literature Review (RSL) on the gamification technique applied in higher education in Administration and Accounting Sciences, a practice that can contribute to the teaching-learning process by providing students with greater commitment to knowledge construction. The research was carried out in the Web of Science and Science Direct databases and, although an initial year for the searches was not established, these were limited to the month of April of the year 2022, using the keywords ’gamification’ and ’accounting education’; ’gamification’ and ’business education’; ’gamification’ and ’accounting’; ‘gamification’ and ‘management’. In line with the inclusion criteria, 18 studies were selected because they met the objective proposed in this study. Among other results, it is highlighted that gamification is a methodological practice that can be used in the classroom in higher education of Administration and Accounting, with positive results. However, it is pointed out as a technique that should be better observed by higher education professors, taking into account that improving teaching practice is an imminent necessity.